Frequency of toothbrushing in children under 12 years old in Peru, 2019 2021 - Cabanillas-Yllesca, Karen; León-Manco, Roberto Antonio; Del Castillo-López, César Eduardo; Beltrán , Jorge Arturo; Garcés-Elías, María Claudia (Revista Facultad de Odontología Universidad de Antioquia, 2024)
Intoduction: having adequate hygiene could help prevent oral diseases such as dental caries. The objective of this study was to determine the practice of toothbrushing in Peruvian children under 12 years of age between 2019 and 2021. Methods: a cross-sectional, analytical, and retrospective analysis was done by using the data from the 2019,2020 and 2021 Demographic and Family Health Survey databases. 38 203 records were obtained in 2019, 18 613 in 2020, and 35 759 in 2021. The variables were general, daily, and minimum two times a day toothbrushing, natural region, area and place of residence, altitude, wealth index, health insurance coverage, age, and sex. A descriptive, bivariate, and multivariate statistical evaluation was carried out. Results: general toothbrushing was 94.93% (n=83,032), daily toothbrushing was 86.32% (n=67,753), and at least twice a day was 82.93% (n=53,824). In the multivariate form, the year 2020 showed a negative association with daily toothbrushing (RPa: 0.97; 95% CI: 0.96-0.99; p<0.001) and at least twice a day (RPa: 0.96; 95% CI: 0.95-0.98; p<0.001). The year 2021 revealed a negative association with general toothbrushing (RPa:0.98; 95%CI: 0.97-0.98; p<0.001), daily (RPa:0.97; 95%CI: 0.95-0.98; p<0.001) and minimum twice a day (RPa: 0.94; 95%CI: 0.92-0.96; p<0.001), adjusted for the previously associated covariates. Conclusion: the studied years were negatively associated with general toothbrushing, daily toothbrushing, and toothbrushing minimum twice daily.